EDUKASI PERSONAL HYGIENE PADA LANSIA DI LINGKUNGAN WILAYAH KELURAHAN RAWABUAYA: PERSONAL HYGIENE EDUCATION IN THE ELDERLY ENVIRONMENT - Arni Safdiantina (Sekolah Tinggi Ilmu Kesehatan Kesetiakawanan Sosial Indonesia, 2021)
The problem that arises in the elderly is the difficulty of maintaining and improving the health of the elderly. The problem of hygiene is less attention to the elderly, this happens because the elderly consider hygiene problems as an unimportant problem, even though a disease can occur and affect health. It is known that most of the elderly have many diseases, one of which is the personal hygiene factor. This activity aims to provide education to the elderly in an effort to maintain the personal hygiene of the elderly. Through this activity, it was illustrated that all elderly participants seemed enthusiastic and had increased knowledge about the importance of personal hygiene as reflected in the ability to answer questions related to the educational materials provided